GRI STANDARDS-BASED SUSTAINABILITY REPORTING DISCLOSURE PRACTICES ACROSS COUNTRIES - Rein Yosua Yehezkiel; Christina Dwi Astuti; Ice Nasyrah Noor (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2023)
The disclosure of sustainability reports based on GRI standards between countries has become a new trend in recent years. This is driven by various factors, such as increasing awareness of sustainability issues, increasing information demands from investors and other stakeholders, and increasing the number of sustainability reporting standards available. This study aims to determine the level of disclosure of sustainability reports in companies engaged in the basic materials and energy industry sector in developed countries (UK, Germany and France) and developing countries (Indonesia, Malaysia and Thailand). The content analysis method is used in this study to assess the content of sustainability reports or integrated company annual reports of 269 selected companies listed in the basic material and energy sectors of the stock exchanges of each country within the period 2019 to 2022. Based on the results of the analysis, it was concluded that the level of sustainability disclosure in accordance with GRI Standards in developed countries is higher than in developing countries for all sectors. In addition, it is also found that there are differences in the completeness of the presentation of sustainability topics where environmental topics are topics that are more fully presented in developed countries in all sectors than in developing countries which are more complete in presenting social topics in all sectors.